Implementasi Perda Kabupaten Bengkulu Utara Nomor 4 Tahun 2016 Tentang Ketertiban Umum Dan Ketenteraman Masyarakat Dalam Wilayah Kabupaten Bengkulu Utara - Susanto, Yohanes Yohanes; Hairani, Wita; Wiji Rahayu, Shinta (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study is a descriptive research using a qualitative approach, aiming to describe and analyze the implementation of Regional Regulation Number 4 of 2016 of North Bengkulu Regency concerning Public Order and Community Tranquility. The research focuses on the execution of the policy by the Civil Service Police Unit (Satpol PP) and the obstacles encountered in maintaining public order within the region. The findings indicate that the policy implementation is generally aligned with the objectives of the regulation, particularly in creating a peaceful, orderly, and harmonious social environment. The availability of human resources is considered sufficient, communication between agencies is running effectively, and tasks are carried out using persuasive and humanistic approaches. However, the effectiveness of the policy still faces several challenges, including limited budget allocation, low public awareness, weak enforcement of sanctions, and a shortage of personnel. Based on these findings, it is recommended that the local government increase budget support, enhance public legal awareness through continuous socialization and education, and strengthen cross-sectoral coordination. Additionally, the provision of legal vending zones for street vendors is needed to prevent disruption to public order, alongside the enforcement of regulations that are firm yet humanistic